The influence of technical performance indicators on the results of the Chinese Football Super League at different stages of the season-based on evidence from the 2010-2019 seasons - Ma, X.; Li, X.; Quan, T.; Liu, H.; Liu, T. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
This study explored the different influences of technical indicators on match results in different stages of football league play. Sample data from 2400 Chinese Super League matches during 2010-2019 were divided into three season stages according to round sequence: the early stage (1-10 rounds), the middle stage (11-20 rounds), and the late stage (21-30 rounds). A two-way, fixed-effect ordered logit model was then constructed and used, together with Fisher`s combination test, to compare regression results. The study results showed that: (1) when controlling for other variables, as the league progresses, an increase in goals will gradually increase the possibility of better match results, and this increase shows significant differences between the early and late stages (p < 0.05). The possibility of better match results by an extra goal is 0.075 times higher in the late stage than the early stage. (2) While maintaining all control variables, as the season progresses, the increase in red card penalties will gradually multiply the probability of worse match outcomes, and this increase is also significantly different between the early and middle stages and between the early and late stages (p < 0.05). The possibility of worse match outcomes due to the presence of an extra red card is 0.377 times higher in the middle stage and 0.476 times higher in the late stage than the early stage.